2019
DOI: 10.1016/j.jsps.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal patches loaded with L-cysteine HCL as a strategy for protection from mobile phone emitting electromagnetic radiation hazards

Abstract: Mobile phone usage has been increased in the last few years emitting electromagnetic radiation (EMR), which disturbs normal cellular processes via oxidative stress. L-cysteine, a glutathione precursor, prevents oxidative damage. Transdermal patches (TDPs) loaded with L-cysteine hydrochloride (L-CyS-HCL) were fabricated by dispersion of L-CyS-HCL 5% w/w and different concentrations of sorbitol as a plasticizer in room-temperature vulcanizable synthetic silicone matrices (RTV-Si). The effect of sorbitol on patch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…Relevant literature has shown that electromagnetic radiation from phones can cause neurasthenia, chest tightness, palpitations, and other diseases, and can accelerate glucose metabolism in the brain [6]. Keangin et al calculated the SAR of liver tissue, as well as the effects of tissue temperature increase, using single-slit and double-slit coaxial antennas [7].…”
Section: Introductionmentioning
confidence: 99%
“…Relevant literature has shown that electromagnetic radiation from phones can cause neurasthenia, chest tightness, palpitations, and other diseases, and can accelerate glucose metabolism in the brain [6]. Keangin et al calculated the SAR of liver tissue, as well as the effects of tissue temperature increase, using single-slit and double-slit coaxial antennas [7].…”
Section: Introductionmentioning
confidence: 99%
“…Kecepatan internet dalam 4G dapat mencapai 100 Mbps sehingga aplikasi yang membutuhkan kecepatan sangat tinggi seperti game online, streaming video definisi tinggi dan TV interaktif dapat dinikmati (Patel et al, 2018). Telepon seluler telah lama diketahui memancarkan radiasi gelombang elektromagnetik (Omar et al, 2018). Secara definisi radiasi merupakan cara perambatan energi ke lingkungannya tanpa membutuhkan medium atau bahan pengantar tertentu (Ancila & Hidayanto, 2016) dan gelombang elektromagnetik adalah gelombang yang dihasilkan dari partikel bermuatan listrik yang bergerak dan terbentuk dari rotasi elektron di dalam atom dan intinya (Kaplan et al, 2015).…”
unclassified